KEEFEKTIFAN METODE DEMONSTRASI DALAM PEMBELAJARAN MEMAHAMI TEKS PROSEDUR SISWA SMP NEGERI 1 KEFAMENANU - Kresensia Luruk; Metropoly Merlin J. Liubana; Iswan Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the ability of seventh-grade students at SMP Negeri 1 Kefamenanu to understand procedural texts through the demonstration method. A descriptive quantitative normative research design was employed in this study. Data were collected using a test to measure students' comprehension and a questionnaire to assess their responses to the implementation of the demonstration method. The data were analyzed by calculating the scores and mean values of both the test and questionnaire results. The findings revealed that students' comprehension of procedural texts reached 84.61%, which was categorized as achieving mastery. Meanwhile, students' responses to the implementation of the demonstration method reached 83.33%, indicating that the method was considered highly beneficial. On the other hand, the percentage of students who did not achieve mastery was 15.38%, while 16.66% of the respondents considered the method not beneficial. It can therefore be concluded that the implementation of the demonstration method in teaching procedural texts to seventh-grade students at SMP Negeri 1 Kefamenanu was effective.